2014
DOI: 10.1021/am503963b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallization of Cu2ZnSnSxSe4–x Counter Electrode on the Performance for Efficient Dye-Sensitized Solar Cells

Abstract: Cu2ZnSnSxSe4-x (CZTSSe) counter electrodes (CEs) in dye-sensitized solar cells (DSSCs) are commonly developed with porous structures, but their high surface area could also retard electron transport processes owing to the abundant grain boundaries. Herein, we employed a convenient solution method and a rapid heating process to prepare well crystalline CZTSSe CEs in DSSCs. The influence of crystallization of CZTSSe film on DSSCs performances was discussed in depth. The thermogravimetric analysis, phase morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Therefore, it is very likely that the value of R ct would not influence the FF value to a large extent in our case, as supported by some literatures that there is no clear correlation between the values of FF and R ct . [50][51][52][53][54] In fact, some literatures reported that the FF value is influenced by the R ct value, i.e., the larger the R ct , the smaller the FF. [55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures.…”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very likely that the value of R ct would not influence the FF value to a large extent in our case, as supported by some literatures that there is no clear correlation between the values of FF and R ct . [50][51][52][53][54] In fact, some literatures reported that the FF value is influenced by the R ct value, i.e., the larger the R ct , the smaller the FF. [55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures.…”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
“…[55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures. [50][51][52][53][54] This study reports on the preparation of Ti plates with TNT imprints and their applications on …”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
“…[1][2][3][4] In general, supercapacitors can be classied into electric double layer capacitors (EDLCs) and pseudocapacitors on the basis of their charge storage modes. 10,11 Transition-metal oxides, hydroxides, and conducting polymers are demonstrated in supercapacitor applications based on their pseudocapacitive properties. Carbon-based materials such as activated carbon, carbon nanocages and graphene have been widely used as electrodes for EDLCs due to their high specic-areas, good electrical conductivities, long cycle lifetimes and low costs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the CZTS nanocrystal films are more compact and dense compared with the CZTSSe films, which were fabricated by the same solution process. Generally speaking, it is undesirable for the existence of pore in the absorbing layer of thin film solar cell, however, the porous structure was beneficial to form well crystallization and large grain CZTSSe thin films in the following selenization process [31]. To further investigate the phase composition and phase structure of as-prepared CZTSSe film and selenized CZTSSe film, XRD measurements were carried out.…”
Section: Resultsmentioning
confidence: 99%